Diagnostic role of circulating MiR-21 in colorectal cancer: a update meta-analysis - Liu, Tong (Ann Med, 2020)
AIM: MicroRNA-21 is an oncogenic miRNA that modulates the expression of multiple cancer-related target genes. We conducted this meta-analysis to assess diagnostic role of circulating miR-21 in CRC, hoping to choose the best biomarker in CRC diagnosis. METHODS: We searched the PubMed, CNKI and WanFang database to identify records related to diagnostic role of circulating miR-21 in CRC. The search words were “microRNA-21”, “miRNA-21”, “colorectal cancer”, “colorectal carcinoma” and “diagnosis”. The searched articles were published before 14(th) July 2020. RESULTS: We got 18 studies to conduct this meta-analysis including 1129 blood specimens of CRC patients and 951 control specimens. The meta-analysis showed that the pooled sensitivity and specificity of circulating miR-21 for CRC diagnosis were 77% (95% CI, 70–82) and 83% (95% CI, 78–88). The combined positive likelihood ratio (PLR) was 4.20 (95% CI, 3.12–5.66) and the combined negative likelihood ratio(NLR) was 0.30 (95% CI, 0.23–0.38). The diagnostic odds ratio (DOR) was 16.48 (95% CI 10.09–26.91) and the area under the summary receiver operating characteristic curve (SROC) for the included studies was 0.87(95%CI, 0.84–0.90). CONCLUSION: Our meta-analysis results suggest that circulating miR-21 has a potential diagnostic value with moderate sensitivity and good specificity for CRC.